Apt (Adenine Phosphoribosyltransferase) Mutation in Laboratory-Selected Vancomycin-Intermediate Staphylococcus aureus - Reena Lamichhane-Khadka; Santosh Dulal; Jesus A. Cuaron; Richard Pfeltz; Sushim Kumar Gupta; Brian J. Wilkinson; John E. Gustafson (MDPI AG, 2021)
Comparative genomic sequencing of laboratory-derived vancomycin-intermediate Staphylococcusaureus (VISA) (MM66-3 and MM66-4) revealed unique mutations in both MM66-3 (in apt and ssaA6), and MM66-4 (in apt and walK), compared to hetero-VISA parent strain MM66. Transcriptional profiling revealed that both MM66 VISA shared 79 upregulated genes and eight downregulated genes. Of these, 30.4% of the upregulated genes were associated with the cell envelope, whereas 75% of the downregulated genes were associated with virulence. In concordance with mutations and transcriptome alterations, both VISA strains demonstrated reduced autolysis, reduced growth in the presence of salt and reduced virulence factor activity. In addition to mutations in genes linked to cell wall metabolism (ssaA6 and walK), the same mutation in apt which encodes adenine phosphoribosyltransferase, was confirmed in both MM66 VISA. Apt plays a role in both adenine metabolism and accumulation and both MM66 VISA grew better than MM66 in the presence of adenine or 2-fluoroadenine indicating a reduction in the accumulation of these growth inhibiting compounds in the VISA strains. MM66 apt mutants isolated via 2-fluoroadenine selection also demonstrated reduced susceptibility to the cell wall lytic dye Congo red and vancomycin. Finding that apt mutations contribute to reduced vancomycin susceptibility once again suggests a role for altered purine metabolism in a VISA mechanism.